2006
DOI: 10.1098/rstb.2006.1918
|View full text |Cite
|
Sign up to set email alerts
|

Towards a conceptual and operational union of bacterial systematics, ecology, and evolution

Abstract: To completely understand the ecology of a bacterial community, we need to identify its ecologically distinct populations (ecotypes). The greatest promise for enumerating a community's constituent ecotypes is held by molecular approaches that identify bacterial ecotypes as DNA sequence clusters. These approaches succeed when ecotypes correspond with sequence clusters, but some models of bacterial speciation predict a one-to-many and others a many-to-one relationship between ecotypes and sequence clusters. A fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(192 citation statements)
references
References 97 publications
(147 reference statements)
4
183
0
5
Order By: Relevance
“…Cluster II or the 'PCCA ecotype' occurs as a group with 99% similarity ('microdiversity cluster'), at a variety of different loci (ITS, cpcBA gene and cpcBA-IGS analysis). Previous studies indicate that such microdiversity clusters could represent important units of differentiation as ecotypes in natural populations of bacteria (Palys et al, 1997;Moore et al, 1998;Rocap et al, 2003;Konstantinidis and Tiedje, 2005;Lopez-Lopez et al, 2005;Thompson et al, 2005;Cohan, 2006;Polz et al, 2006;Cohan and Perry, 2007), and are often observed in environmental clone libraries (Field et al, 1997;Acinas et al, 2004;Morris et al, 2005;Johnson et al, 2006;Pommier et al, 2007). The microdiversity clusters identified here are correlated with morphological and ecophysiological traits such as cell length and the capacity to perform CCA (Figures 4 and 5), providing further support for the designation as an ecotype (Ahlgren and Rocap, 2006;Johnson et al, 2006;Polz et al, 2006;Ward et al, 2006).…”
Section: Genetic Diversification Of Pseudanabaena Populationsmentioning
confidence: 57%
“…Cluster II or the 'PCCA ecotype' occurs as a group with 99% similarity ('microdiversity cluster'), at a variety of different loci (ITS, cpcBA gene and cpcBA-IGS analysis). Previous studies indicate that such microdiversity clusters could represent important units of differentiation as ecotypes in natural populations of bacteria (Palys et al, 1997;Moore et al, 1998;Rocap et al, 2003;Konstantinidis and Tiedje, 2005;Lopez-Lopez et al, 2005;Thompson et al, 2005;Cohan, 2006;Polz et al, 2006;Cohan and Perry, 2007), and are often observed in environmental clone libraries (Field et al, 1997;Acinas et al, 2004;Morris et al, 2005;Johnson et al, 2006;Pommier et al, 2007). The microdiversity clusters identified here are correlated with morphological and ecophysiological traits such as cell length and the capacity to perform CCA (Figures 4 and 5), providing further support for the designation as an ecotype (Ahlgren and Rocap, 2006;Johnson et al, 2006;Polz et al, 2006;Ward et al, 2006).…”
Section: Genetic Diversification Of Pseudanabaena Populationsmentioning
confidence: 57%
“…Evidence for ecotypes: vertical stratification and seasonality Ecotypes are similar phylogenetic subgroups of bacteria that differ in physiological details that determine niche specificity (Cohan, 2006). Patterns of variation in time and space are often used to identify ecotypes.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that selective sweeps may periodically purge genetic variation from coexisting genomes (Cohan 2002(Cohan , 2006. This assumes that clonally reproducing bacteria will accumulate mutations, which, in rare cases, are adaptive.…”
Section: Sequence Clusters As Populations or Species?mentioning
confidence: 99%